Evaluation of an experiential training program in patient-centered outcomes and comparative effectiveness research for diverse researcher communities and health care organizations - Dedra S. Buchwald; Megan H. Rogers; Barbara A. Rose; Brian W. Bresnahan; Beth Devine; Linda LeResche; Lonnie A. Nelson; Donald L. Patrick; Danielle C. Lavallee; Michelle M. Garrison; Andrew A. White; Larry G. Kessler (Journal of Clinical and Translational Science, 2023)
Abstract